Analysis of Mother Behavior Factor in Following Program of Breastfeeding Support Group in the Region of Asemrowo Health Center, Surabaya - Esti Yunitasari; Alfiani Triningsih; Retnayu Pradanie (NurseLine Journal, 2019)
Breastfeeding support group is an activity consisting of 6-12 people mother with infants aged 0-6 months gathered regularly 2 weeks. Mothers can get support from people who are experiencing the same situation. Because members of this program have similar experiences and environmental situations, a mutually supportive atmosphere will be more easily established. However this program has not been implemented maximally in some areas including Asemrowo Health Center,, which resulted in exclusive breastfeeding coverage in Asemrowo sub-district has not reached the national target that only 58.22%. This study aims to determine the factors associated with maternal behavior in following the breastfeeding support group in the region of Asemrowo health center, Surabaya. This was cross sectional design. The populations were 64 mothers who have an infant in 0-6 month at the region of Asemrowo Health Center, Surabaya using total sampling technique. There were five variables in this study, there are knowledge, attitude, belief, culture as independent variable and behavior as dependent variable. The instrument used a modified questionnaire from previous research and tested validity and reliability with validity results of 0.350-0.916 and reliability of 0.663 for knowledge questionnaires, 0.723 attitude questionnaires, 0.632 belief questionnaires, 0.863 cultural questionnaires, and 0.948 behavior questionnaires. Data analyze using spearman rank correlation with significance level α≤0,05. Statistical test result p= 0.00 r= 0,457 for knowledge with behavior, p= 0.011 r= 0,315 for attitude and behavior, p= 0,035 r= 0,264 for belief and behavior, p= 0.003 r= 0,360 for culture and behavior. The result had showed that was correlation between knowledge with behavior, attitude with behavior, belief with behavior and culture with behavior. Provision of health counseling and promotion by health workers on the importance of participating in Breastfeeding support group program to mothers with infants aged 0-6 months is needed so that mothers can provide exclusive breastfeeding.